Contributions to the geomorphology, geology and volcanology of Costa Rica from Alexander von Frantzius - Vargas, Asdrubal (2014)
In this work it will be describe the contribution to the geosciences from the German scientific Alexander von Frantzius, who was pioneer in the exploration and description of the geological and geomorphological environmental of some regions in Costa Rica in the second half of the XIX century. Joined to his medical activities he explored the Reventazón river, Pirris and Tempisque valley and described the outcrops of rocks, and hidrological, hidrogeological and geomorphological features of them. These descriptions were presented through articles in journals in German language and translated in Spanish some decades later